PENGEMBANGAN MODEL PEMBELAJARAN JIGSAW DI MADRASAH IBTIDAIYAH - Siti Fatimah; Jihan Fadhilah, Seftia Eka Asmara, Ajeng Bunga Putria, Salsyabina Puspita Ayu (CV. ADIBA ASIHA AMIRA, 2023)
The purpose of this research is to produce a deep Jigsaw learning model product in order to develop students' creative thinking skills in science learning Social in Madrasah Ibtidaiyah. This research was conducted using a research and development approach. A validation test was performed on five madrasas with qualifications that are considered good, medium, and poor. This research was developed by way of experimentation and comparing models of jigsaw learning (KE) with conventional learning (KK). Test results validation showed that students' ability to think creatively turned out different between the test results of the experimental group (α ≤ .0001) and the group control (α≤ .0001). The results of this study concluded that: Jigsaw is a multifunctional structure of collaborative learning structures. Jigsaw can be used in several ways to achieve various goals but is mainly used for presentations and getting new material, this structure creates interdependence. Jigsaw-type cooperative learning is a learning method based on the multifunctional structure of study groups that can be used on all subjects and all levels to develop the expertise and skills of each group that they have previously learned at expert team meetings. In the jigsaw type cooperative learning model, there are home groups and expert groups. Home group, namely the parent group of students consisting of students with diverse abilities, gender, and family backgrounds. Expert groups, namely groups of students consisting of members of different home groups are assigned to study the topic and then explain it to members of the home group. The expert group is a combination of several experts from the original group.